Environmental Modifications and 2-Year Measured and Self-reported Stair-Use: A Worksite Randomized Trial - Graham, Dan J. (2013)
Environmental modifications have been shown to increase short-term stair use, longer-term success is unclear. This study assessed the 2-year effectiveness of an environmental intervention promoting worksite stair use. We assessed stair use at work by means of self-reports and infrared beam counters (which send a safe and invisible beam of infrared light from one side of a stairwell to a reflector on the other side; when an individual uses the stairs, the infrared beam is disrupted and an instance of stair use is recorded) at six worksites (three intervention, three control) in a group randomized, controlled worksite weight-gain prevention trial in Minneapolis/St. Paul, MN. Intervention modifications were signs encouraging stair use, music, and art posters in stairwells. We collected data before environmental modifications (2006–2007) and at the end of the 2-year intervention (2008–2009). The intervention had a significant positive effect on stair use measured both objectively and via self-report, with greatest increases reported among those participants who used the stairs least at baseline. Following 2-years of continuously-maintained stairwell modifications, increases in both objectively-measured and self-reported stair use were significantly larger at intervention than control worksites. Study findings suggest that the positive impact of environmental modifications on stair use persist over a longer time period than has been previously demonstrated. Results also indicate that infrequent stair users may be most amenable to the behavior changes encouraged by these environmental enhancements.